Paseban House Model: Design of Learning Model in the ICT- Based Pancasila Student Profiles Strengthening Project - Agus Hasbi Noor; Ansori Ansori; Tiffany Estherlita; Ririn Hunafa Lestari; Prima Suci Rohmadheny (Journal of Nonformal Education, 2024)
The decline in trust in the values of Pancasila, which has led to intolerance, violence against children and women, bullying, pornography, drug abuse, and technological disruption, poses challenges in the school environment. To address these issues, it is necessary to have learning that develops character values ​​through the Pancasila Student Profile Strengthening Project (P5) using the Paseban house model based on local wisdom representing Pancasila values ​​utilizing Information Communication And Technology (ICT). Therefore, the aim of this research was to develop a P5 learning design through an ICT-based Paseban House model. The learning design was developed using the Educational Design Research (EDR) method analyzed through a thematic approach based on the stages of EDR method. The research results showed a crisis in students’ character as they enter adolescence, manifesting in violent behavior, decreasing respect and honor, a lack of responsibility and honesty, thus necessitating learning to prevent this crisis through the P5 learning design with the Paseban house model based on local customs and culture values. To facilitate P5 learning with the Paseban house model, this learning design utilized ICT, specifically the Learning Management System (LMS), as an easily accessible learning innovation regardless of time and place due to the rapid technological advancements and the spread of COVID-19.